Analytical and graphical methods for the solution of one problem of transport logistics - Zhetpisov, K.; Karbenova, N.G. (KSU Publ., 2017)
This article shows the way to solve a specific problem of transport logistics using the potential method. The first support plan is constructed by the method of the north-western corner. The article also shows a graphical method for solving the problem. The article shows the optimal method for solving the problem of transport logistics using the example of the real economy of the Kostanay region (Arkalyk).
Транспорттық логистиканың бiр проблемасын шешудiң аналитикалық және графиктiк әдiстерi
Аналитический и графический методы решения одной проблемы транспортной логистики
Keywords: Logistics; transport task; potencial; northwest corner; count; bipartite count; value; volume